2020
DOI: 10.1007/s11920-020-1136-7
|View full text |Cite
|
Sign up to set email alerts
|

Services for Adults With Autism Spectrum Disorder: a Systems Perspective

Abstract: Purpose of Review We review original research about services for adults on the autism spectrum published from January 2013 through December 2018. The main aim is to characterize the topical and methodological aspects of research about services. We review research on services related to employment, living in the community, and social participation. We compare our results with those from a similar review published in 2012 to assess progress and identify where new directions in research about services for adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 88 publications
0
45
0
Order By: Relevance
“…sense of coherence; Helles et al 2017), but as yet there is no robust framework for integrating these objective and subjective domains. Hence, although traditional measures of outcome are important, for example for comparisons with other groups of individuals (Shattuck et al 2020), consideration of each individual's perspective is vital in helping to define what "success" really means. Following from this, future research should seek to integrate the autistic person's valued "beings" and "doings" (thought to be central to some objective-subjective theories of quality of life; e.g.…”
Section: Discussionmentioning
confidence: 99%
“…sense of coherence; Helles et al 2017), but as yet there is no robust framework for integrating these objective and subjective domains. Hence, although traditional measures of outcome are important, for example for comparisons with other groups of individuals (Shattuck et al 2020), consideration of each individual's perspective is vital in helping to define what "success" really means. Following from this, future research should seek to integrate the autistic person's valued "beings" and "doings" (thought to be central to some objective-subjective theories of quality of life; e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Most included studies (67%) were pharmacological trials, with the main focus being on the reduction of behavioral problems or autistic symptoms, such as repetitive or ritualistic behaviors; none focused on improving quality of life, social participation or emotional well-being. Lack of progress in adult intervention research is confirmed in a more recent review by Shattuck et al (2020) who identified only 52 papers (i.e. < 1% of over 23,000 peer-reviewed studies on autism) that had a focus on support systems, services or intervention programs for autistic adults.…”
Section: Interventions For Adults With Autismmentioning
confidence: 98%
“…describe the provision of autism services across the lifespan and coordination of autism services across different systems as experienced by service providers and users, and 2. identify barriers to accessing services or gaps in service coordination from the perspectives of service providers and users. Shattuck et al (2020) have emphasised the importance of taking a life course, systems approach to autism services research. A life course approach recognises the changes autistic people may experience in the availability and quality of services over their lifetime, while a systems approach can provide greater insight into how the complex range of autism service systems functions, interacts and can be improved.…”
Section: Study Contextmentioning
confidence: 99%
“…Thus, this study adopted a life course, systems approach to understand the current provision and coordination of autism services in Singapore, as well as to identify areas of improvement towards achieving a comprehensive and integrated service landscape that is able to meet the needs of autistic individuals and their families. Furthermore, Shattuck et al (2020) also called for greater involvement of different stakeholders, including service providers and users, in the improvement of autism service systems. While this study focuses more on the perspectives of service providers, efforts were made to include the views of some autistic adults and caregivers/parents of autistic children to gain a more holistic understanding of the topic at hand.…”
Section: Study Contextmentioning
confidence: 99%